For which decisions is Shared Decision Making considered appropriate? – A systematic review. (January 2023) - van der Horst, Dorinde E.M.; Garvelink, Mirjam M.; Bos, Willem Jan W.; Stiggelbout, Anne M.; Pieterse, Arwen H.
Abstract: Objective: To identify decision characteristics for which SDM authors deem SDM appropriate or not, and what arguments are used. Methods: We applied two search strategies: we included SDM models from an earlier review (strategy 1) and conducted a new search in eight databases to include papers other than describing an SDM model, such as original research, opinion papers and reviews (strategy 2). Results: From the 92 included papers, we identified 18 decision characteristics for which authors deemed SDM appropriate, including preference-sensitive, equipoise and decisions where patient commitment is needed in implementing the decision. SDM authors indicated limits to SDM, especially when there are immediate life-saving measures needed. We identified four decision characteristics on which authors of different papers disagreed on whether or not SDM is appropriate. Conclusion: The findings of this review show the broad range of decision characteristics for which authors deem SDM appropriate, the ambiguity of some, and potential limits of SDM. Practice implications: The findings can stimulate clinicians to (re)consider pursuing SDM in situations in which they did not before. Additionally, it can inform SDM campaigns and educational programs as it shows for which decision situations SDM might be more or less challenging to practice. Highlights: In half of the SDM models, authors explicitly described when SDM is appropriate . Authors considered SDM appropriate for a broad range of decisions. For some decision characteristics, authors disagreed on whether or not SDM is appropriate. Authors' examples of when SDM is (in)appropriated came from a range of settings.